Loss of Active Neurogenesis in the Adult Shark Retina - Hernández-Núñez, Ismael; Robledo, Diego; Mayeur, Hélène; Mazan, Sylvie; Sánchez, Laura; Adrio, Fátima; Barreiro-Iglesias, Antón; Candal, Eva (Frontiers in Cell and Developmental Biology, 2021)
Neurogenesis is the process by which progenitor cells generate new neurons. As development progresses neurogenesis becomes restricted to discrete neurogenic niches, where it persists during postnatal life. The retina of teleost fishes is thought to proliferate and produce new cells throughout life. Whether this capacity may be an ancestral characteristic of gnathostome vertebrates is completely unknown. Cartilaginous fishes occupy a key phylogenetic position to infer ancestral states fixed prior to the gnathostome radiation. Previous work from our group revealed that the juvenile retina of the catshark Scyliorhinus canicula, a cartilaginous fish, shows active proliferation and neurogenesis. Here, we compared the morphology and proliferative status of the retina in catshark juveniles and adults. Histological and immunohistochemical analyses revealed an important reduction in the size of the peripheral retina (where progenitor cells are mainly located), a decrease in the thickness of the inner nuclear layer (INL), an increase in the thickness of the inner plexiform layer and a decrease in the cell density in the INL and in the ganglionar cell layer in adults. Contrary to what has been reported in teleost fish, mitotic activity in the catshark retina was virtually absent after sexual maturation. Based on these results, we carried out RNA-Sequencing (RNA-Seq) analyses comparing the retinal transcriptome of juveniles and adults, which revealed a statistically significant decrease in the expression of many genes involved in cell proliferation and neurogenesis in adult catsharks. Our RNA-Seq data provides an excellent resource to identify new signalling pathways controlling neurogenesis in the vertebrate retina.